Stability of ultraviolet-cured chitosan coating on cotton gauze for water filtration. (March 2019) - Truffa Giachet, Francesca; Periolatto, Monica; Sanchez Ramirez, Diego Omar; Carletto, Riccardo Andrea; Varesano, Alessio; Vineis, Claudia; Bongiovanni, Roberta
Cotton gauzes coated with chitosan have been tested as water filter for biological disinfection against Gram-positive bacteria. The present study develops the previous ones, aiming to the stability evaluation of ultraviolet-cured chitosan coating of cotton gauzes in order to optimize the chitosan amount applied to the substrate, lowering the add-on percentage as much as possible: 10%, 5% and 2% wt were here considered. Antibacterial activity and permanence of this property after water flow were tested, showing good results, in particular as regards 10% wt and 5% wt chitosan coated cotton gauze. Moreover, chitosan release was studied in both static and dynamic conditions, with the result that water flux causes a reduction of the amount of chitosan, which remains bounded to the fibres. This reduction depends on the duration of the flux and on the original amount of chitosan on the filter.